Spatial privacy on institutions for unaccompanied teenage girls in Mashhad-Iran - Nazanin Salehi Milani,; Azizah Salim Syed Salim,; Norsidah Ujang, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2013)
Nations, according to their beliefs and to their community found a solution to shelter unaccompanied teenage girls regardless of its suitability and positions. This study intends to provide some insight into the ways to improve designing of residential care for unaccompanied teenage girls according to their preferences in Mashhad, Iran. The main difficulty in the context of Mashhad and Iran is the lack of private places and large number of children in residential care. A quantitative approach has been conducted to study the effect of privacy on teenage girls aged 12- 18 (n=67) living in 5 selected residential care in Mashhad. This research suggests new application and directions and appropriate size in terms of spatial privacy for teenage girls in the future.